2007
DOI: 10.1103/physrevlett.98.239902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Current and Strain-Induced Spin Polarization inInGaN/GaNSuperlattices [Phys. Rev. Lett.98, 136403 (2007)]

Abstract: The lateral current-induced spin polarization in InGaN/GaN superlattices (SLs) without an applied magnetic field is reported. The fact that the sign of the nonequilibrium spin changes as the current reverses and is opposite for the two edges provides a clear signature for the spin Hall effect. In addition, it is discovered that the spin Hall effect can be strongly manipulated by the internal strains. A theoretical work has also been developed to understand the observed strain induced spin polarization. Our res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
(40 reference statements)
3
25
0
Order By: Relevance
“…While in classical spintronics the spin dynamics is mainly controlled by exchange interactions, in orbital spintronics the central role is played by the spin-orbit (SO) interaction, which allows direct manipulation of the spins by electric fields. [23][24][25][26][27][28][29][30][31][32][33][34] In recent years both the exchange interaction-based approach and the spin-orbit interaction-based one have been shown to be viable for achieving current-induced switching of the magnetization of a ferromagnetic metal. 26,[35][36][37][38][39] Although spin-orbit interactions are generally much weaker than exchange interactions, they are known to produce a characteristic linear in momentum spin splitting of surface states -the so-called Rashba effect 40 , which is observed in semiconductor as well as metallic interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…While in classical spintronics the spin dynamics is mainly controlled by exchange interactions, in orbital spintronics the central role is played by the spin-orbit (SO) interaction, which allows direct manipulation of the spins by electric fields. [23][24][25][26][27][28][29][30][31][32][33][34] In recent years both the exchange interaction-based approach and the spin-orbit interaction-based one have been shown to be viable for achieving current-induced switching of the magnetization of a ferromagnetic metal. 26,[35][36][37][38][39] Although spin-orbit interactions are generally much weaker than exchange interactions, they are known to produce a characteristic linear in momentum spin splitting of surface states -the so-called Rashba effect 40 , which is observed in semiconductor as well as metallic interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In semiconductors, there have been experimental reports on the SHE in n-type GaAs [7], p-type GaAs [8] and n-type InGaN/GaN superlattices [9] in recent years. These experimental results have been discussed theoretically, and it is now recognized that the SHE in n-type GaAs is due to the extrinsic mechanisms, i.e., skew scattering and side-jump contributions [10,11], while that in p-type GaAs is mainly caused by the intrinsic mechanism [12,13].…”
mentioning
confidence: 99%
“…Further experiments by Stern et al [23] imaged the spatial distribution of the spin accumulation generated by the spin-Hall effect as well as its behavior in a magnetic field. Chang et al [24] also reported, using photoluminescence, a spin accumulation due to the spin-Hall effect in InGaN/GaN superlattices.…”
Section: Experimental Situationmentioning
confidence: 96%
“…Following that, spin accumulations resulting from spin currents were measured by several groups. [18,19,20,21,22,23,24] In what is surely a new generation of experiments, Valenzuela and Tinkham [25] made use of the fact that a spin current gives rise to a transverse charge current. Relying on a nonlocal technique, their group successfully detected a charge current flowing as a result of a spin current in Al metal.…”
Section: Introductionmentioning
confidence: 99%